Study prevalence of risk factors and clinical presentation of ventral incisional hernia an observational study - Nigam, Anjana; Nirala, S. L.; Bhusakhare, Niraj (International Surgery Journal, 2020)
Background: Incisional hernia is the second most common type of hernia after inguinal hernia. It is a complication of abdominal surgery, reported in up to 11% of patients generally and in up to 20% of those who developed post operative wound infection. The list of predictive factors associated with development of incisional hernia is obesity, diabetes mellitus, steroid, smoking, old age, malnutrition, COPD and type of incision. Methods: This was a hospital based cross sectional observational study carried out from February 2018 - October 2019 in surgery department of Dr. B.R.A.M. Hospital Raipur C.G, with diagnosis of incisional hernia. Total 100 patients were included in the study. Results: In present study the mean age of study subjects was 47.27±13.16 years. Around two-third 64% were females. 40% of perforation and 35% of LSCS cases later develop to Incisional hernia. Risk factors profile showed that 31% were alcoholic, 27% smokers, 48% pre-obese and 5% were obese. 36% were hypertensive, 48% diabetic, and 12% had constipation. 25% had prolonged cough, 35% had surgical site infection, 45% had anemia. Clinical presentation of study subjects showed that 63% had swelling, 33% had swelling and pain and 4% had obstruction. Conclusions: Incisional hernia is more common in female than males and in cases above the age of 45 years. It is more common in patients who underwent the previous surgery on an emergency basis especially in perforation and obstruction and LSCS cases. Risk factors associated with incisional hernia are smoker, alcoholic, obesity, hypertension, diabetes, constipation, prolong cough and anemia.